Blood cadmium in Chinese adults and its relationships with diabetes and obesity - Nie, Xiaomin; Wang, Ningjian; Chen, Yi; Chen, Chi; Han, Bing; Zhu, Chunfang; Chen, Yingchao; Xia, Fangzhen; Cang, Zhen; Lu, Meng; Meng, Ying; Jiang, Boren; et al. (Environmental science and pollution research international, 2016)
The aim of this study is to evaluate blood cadmium levels (BCLs) in Chinese adults and explore whether blood cadmium is associated with diabetes or obesity. This study included 5544 adults from a cross-sectional SPECT-China study. BCL and blood lead level (BLL) was measured by atomic absorption spectrometry. Fasting plasma glucose (FPG) was used to define prediabetes and diabetes. Overweight and obesity were defined by body mass index (BMI). The associations of BCL with prediabetes, diabetes, overweight, and obesity were analyzed by multinomial logistic regression analyses. Medians (interquartile range) of BCL were 1.97 μg/L (0.60–3.82) in men and 1.59 μg/L (0.54–3.51) in women. Subjects in low-economic-status areas and urban areas had significantly higher BCL. BCL in current smokers was significantly higher than in current non-smokers. In the adjusted model, a mild positive relationship between BCL and FPG was found. Meanwhile, the prevalence of prediabetes was increased according to the increase in BCL tertiles. Surprisingly, BCL had a negative relationship with prevalence of overweight. In conclusion, BCL in Chinese adults was much higher than in other developed countries and was influenced by gender, smoking, and residential area. BCL was positively related to prediabetes while negatively related to overweight.